METHODS FOR WORKING WITH DIGITAL LIBRARIES AND DATABASES - Mamatova Muslimakhon Sanjarbek qizi; Abduraxmonov To'raxon (TADQIQOTLAR.UZ, 2024)
Abstract:This  article  explores  effective  methods  for  working  with  digital libraries and databases, focusing on strategies that enhance research efficiency and data accessibility. It examines the various tools and technologies available for navigating digital  collections,  including  advanced  search  techniques,  metadata  utilization,  and data management practices. The article also addresses the importance of digital literacy and user training in maximizing the potential of these resources. By highlighting case studies  and  practical  applications,  it  aims  to  provide  researchers,  educators,  and students with a comprehensive understanding of best practices for leveraging digital libraries and databases in their work.